THE ROLE OF FRANCE IN STRENGTHENING SCIENCE IN SERBIA AND THE WESTERN BALKANS: BETWEEN SCIENTIFIC COOPERATION AND SCIENCE DIPLOMACY - Kolakovic, Aleksandra (Serbian political thought, 2023)
France has a long tradition of cultural and scientific influence in the Balkan region, and historically especially in Serbia and in the countries formed on the territory of the former Yugoslavia (Kingdom of Serbs, Croats and Slovenes, Kingdom of Yugoslavia). The aforementioned influence, which followed its economic and political influence, was founded not only on the basis of the Alliance in the Great War (1914–1918), but primarily on the basis of the education and training of the Serbs and Balkans at the Sorbonne and at other French universities. After returning to their homeland, they not only occupied key positions in the state administration and reached ministerial and prime ministerial positions, but also founded scientific disciplines and chairs at universities and continued cooperation with their French professors and scientists. France, especially in the interwar period, gave scholarships for education, which influenced on the development of scientific cooperation, but also the unofficial recognition of scientists as part of diplomacy. The change of the regime in Yugoslavia in 1945 reduced the intensity of scientific cooperation, but did not interrupt its thread, which we can especially see in the example of Pavle Savić and Vinča. This historically long scientific cooperation, which also showed elements of what we mean today by the term „science diplomacy“, was also a foundation for creating France’s scientific cooperation with Serbia, Montenegro, North Macedonia, Bosnia and Herzegovina and Albania (the countries of the Western Balkans, under which France also includes Kosovo*[1]). Through the analysis of available documents, press and statements of officials, diplomats, as well as scientists participating in joint projects, our main goal is to study the role of France in strengthening scientific cooperation in Serbia and the Western Balkans. One of the tasks is to analyze the achievements, as well as to give recommendations for further cooperation in the field of science. The focus is also on the special importance of the transfer of knowledge and the role of science in the framework of diplomacy, and therefore the role of France in Serbia and the Balkans will also be research through this prism. [1] This designation is without prejudice to status and is in accordance with United Nations Security Council Resolution 1244/1999 and the Opinion of the International of the Court of Justice on the Declaration of Independence of Kosovo